The educational (im)mobilities and status (il)legalities of Cape Verdean youth in Portugal. Issue 13 (3rd October 2018) - Challinor, Elizabeth Pilar; Martins, Filipe
ABSTRACT: Education has played a fundamental role shaping Cape Verdean mobilities and recent increases in educational opportunities for poorer sections of the youth population have raised expectations for a better life. Through a discussion of how modern-day education has become a project of self-realisation, the article provides a detailed analysis of a regime of mobility that encouraged Cape Verdeans to study in vocational colleges in Portugal. It illustrates how the protocols signed between local councils in Cape Verde and the colleges created a responsibility vacuum that caused students to slip into illegality, perpetuating the inequalities which the pursuit of education is intended to redress. The ways in which Cape Verdean youth responded – navigating constraints to create the image of a successful life in Portugal against all odds – elucidate how the power of the moral expectation to succeed led them to work the system and to turn secondary education into a stepping stone for their mobility.